Pengaruh Debt Maturity dan Stock Liquidity terhadap Stock Price Crash Risk - Septiani, Elsi Mobila; Handayani, Dian Fitria (Universitas Negeri Padang, 2025)
This study aims to examine the effect of debt maturity and stock liquidity on stock price crash risk in transportation companies listed on the Indonesia Stock Exchange 2020-2023. The population in this study were 20 transportation companies, while the sample in this study were 80 companies. This study uses secondary data obtained from the official website of the Indonesia Stock Exchange (IDX), namely www.idx.co.id, Yahoo Finance and the company's website using multiple linear regression analysis methods. The results of this study concluded that debt maturity (measured using long-term debt) and stock liquidity has no effect on stock price crash risk.